Language, the Uncanny, and the Shapes of History in Claude Simon's The Flanders Road - Lynn A. Higgins (Studies in 20th & 21st Century Literature, 1985)
Asking whether it is possible to read The Flanders Road both as text and as history the essay studies repetitions that structure the novel as they relate to historical events evoked therein, from the Revolution to the Algerian War. The tangled and looped itinerary of a cavalry retreat finds its analog in the narrative "line"; generic variations emerge when (hi)stories are told again and again; these, and even certain kinds of wordplay make the novel, and ultimately history, seem uncanny. But it is the novel's self-conscious strangeness, as it enfolds historical knowledge, that constitutes a commentary on how history is told and even how it is experienced.
Keywords: The Flanders Road; repetition; structure; Revolution; Algerian War; line; history; experience